DNA demethylation agent 5azadC downregulates HPV16 E6 expression in cervical cancer cell lines independently of TBX2 expression (2020)
HPV16 is the most carcinogenic human papillomavirus and causes >50% of cervical cancers, the majority of anal cancers and 30% of oropharyngeal squamous cell carcinomas. HPV carcinogenesis relies on the continuous expression of the two main viral oncoproteins E6 and E7 that target >150 cellular proteins. Among them, epigenetic modifiers, including DNA Methyl Transferases (DNMT), are dysregulated, promoting an aberrant methylation pattern in HPV-positive cancer cells. It has been previously reported that the treatment of HPV-positive cervical cancer cells with DNMT inhibitor 5-aza-2'-deoxycytidine (5azadC) caused the downregulation of E6 expression due to mRNA destabilization that was mediated by miR-375. Recently, the T-box transcription factor 2 (TBX2) has been demonstrated to repress HPV LCR activity. In the current study, the role of TBX2 in E6 repression was investigated in HPV16 cervical cancer cell lines following 5azadC treatment. A decrease of E6 expression was accompanied by p53 and p21 restoration. While TBX2 mRNA was upregulated in 5azadC-treated SiHa and Ca Ski cells, TBX2 protein was not detectable. Furthermore, the overexpression of TBX2 protein in cervical cancer cells did not allow the repression of E6 expression. The TBX2 transcription factor is therefore unlikely to be associated with the repression of E6 following 5azadC treatment of SiHa and Ca Ski cells. © 2020 Spandidos Publications. All rights reserved.